The Toxic Avenger [videorecording (DVD)] - Kaufman, Lloyd, 1945-; Blair, Will (Composer); Blair, Brooke (Cineverse, 2025)
When a downtrodden janitor, Winston Gooze, is exposed to a catastrophic toxic accident, he's transformed into a new kind of hero: The Toxic Avenger. Now, Toxie must rise from outcast to savior, taking on ruthless corporate overlords and corrupt forces who threaten his son, his friends, and his community. In a world where greed runs rampant, justice is best served radioactive.